Ticks as potential vectors of Mycobacterium leprae: Use of tick cell lines to culture the bacilli and generate transgenic strains. - Jéssica da Silva Ferreira; Diego Augusto Souza Oliveira; João Pedro Santos; Carla Carolina Dias Uzedo Ribeiro; Bruna A Baêta; Rafaella Câmara Teixeira; Arthur da Silva Neumann; Patricia Sammarco Rosa; Maria Cristina Vidal Pessolani; Milton Ozório Moraes; Gervásio Henrique Bechara; Pedro L de Oliveira; et al. (Public Library of Science (PLoS), 2018)
Leprosy is an infectious disease caused by Mycobacterium leprae and frequently resulting in irreversible deformities and disabilities. Ticks play an important role in infectious disease transmission due to their low host specificity, worldwide distribution, and the biological ability to support transovarial transmission of a wide spectrum of pathogens, including viruses, bacteria and protozoa. To investigate a possible role for ticks as vectors of leprosy, we assessed transovarial transmission of M. leprae in artificially-fed adult female Amblyomma sculptum ticks, and infection and growth of M. leprae in tick cell lines. Our results revealed M. leprae RNA and antigens persisting in the midgut and present in the ovaries of adult female A. sculptum at least 2 days after oral infection, and present in their progeny (eggs and larvae), which demonstrates the occurrence of transovarial transmission of this pathogen. Infected tick larvae were able to inoculate viable bacilli during blood-feeding on a rabbit. Moreover, following inoculation with M. leprae, the Ixodes scapularis embryo-derived tick cell line IDE8 supported a detectable increase in the number of bacilli for at least 20 days, presenting a doubling time of approximately 12 days. As far as we know, this is the first in vitro cellular system able to promote growth of M. leprae. Finally, we successfully transformed a clinical M. leprae isolate by inserting the reporter plasmid pCHERRY3; transformed bacteria infected and grew in IDE8 cells over a 2-month period. Taken together, our data not only support the hypothesis that ticks may have the potential to act as a reservoir and/or vector of leprosy, but also suggest the feasibility of technological development of tick cell lines as a tool for large-scale production of M. leprae bacteria, as well as describing for the first time a method for their transformation.